2018
DOI: 10.4103/ijem.ijem_213_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence pattern of key polymorphisms in the Vitamin D receptor gene among patients of Type 2 diabetes mellitus in Northeast India

Abstract: Aims:To investigate the association between Vitamin D receptor gene polymorphisms (BsmI, TaqI and FokI) and type 2 diabetes mellitus in patients in north eastern India.Settings and Design:This was a case control study with 40 cases of type 2 diabetes and 20 controls.Materials and Methods:Genomic DNA was extracted from blood and genotyped for the single nucleotide polymorphism (SNPs) of BsmI [rs1544410], TaqI [rs731236] and FokI [rs2228570] by polymerase chain reaction and gene sequencing. Genotype distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Contrary, Angel et al [39] did not support the hypothesis of a significant contribution of Bsml, Apal and Taql VDR polymorphisms in the etiology of T1DM of Chilean patients. Interestingly, the study of Sarma et al [25] in T2DM patients from north eastern India showed that body weight and BMI were significantly associated with BsmI and TaqI polymorphisms. BsmI was associated with HbA1C, and the frequency of the heterozygous genotype of the BsmI polymorphism was significantly higher in T2DM patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary, Angel et al [39] did not support the hypothesis of a significant contribution of Bsml, Apal and Taql VDR polymorphisms in the etiology of T1DM of Chilean patients. Interestingly, the study of Sarma et al [25] in T2DM patients from north eastern India showed that body weight and BMI were significantly associated with BsmI and TaqI polymorphisms. BsmI was associated with HbA1C, and the frequency of the heterozygous genotype of the BsmI polymorphism was significantly higher in T2DM patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the existence of some studies examining the association between VitD levels, VDR polymorphisms, and T2DM in different populations, the results are not clear [13,14,15,16,17,18,19,20,21,22,23,24,25]. Therefore, in this study we aimed to evaluate the association between 25-hydroxy vitamin D [25(OH)D] levels and polymorphisms in the VDR gene (ApaI, BsmI, FokI, and TaqI) in a group of T2DM Brazilian patients, according to their body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%
“…The current and previously published meta-analyses involving studies were shown in Table 2, Supplemental Digital Content, http://links.lww.com/MD/G216. 56 studies met our requirements, [26,27,28–34,19,35–80] of which 37 studies reported the VDR BsmI (5586 cases and 6484 controls), 31 studies examined the VDR FokI (6525 cases and 7464 controls), 19 studies investigated the VDR ApaI (2593 cases and 3557 controls), and 24 studies explored the VDR TaqI (3221 cases and 4027 controls) with T2DM risk, as shown in Figure 1 and Table 4, Supplemental Digital Content, http://links.lww.com/MD/G216. Among these studies, 25, 22, 6, and 4 of the studies were conducted to analyze Asians, Caucasians, Indians, and mixed populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results of another study show that body weight and BMI were significantly associated with polymorphisms Bsm1 and Taq1, while Bsm1 strongly correlated with elevated HbA1c level. The frequency of the heterozygous genotype of the Bsm1 polymorphism was significantly greater in type 2 diabetics than in controls [70]. A study of this parameter in a group of patients with T2D from India revealed that it was Taq1 and Bsm1 polymorphisms that were closely associated with diabetes [71].…”
Section: Vitamin D Deficiency and Type 2 Diabetes Mellitusmentioning
confidence: 96%